2015
DOI: 10.4142/jvs.2015.16.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT assessment of bone mineral density in dogs with hyperadrenocorticism

Abstract: Canine hyperadrenocorticism (HAC) is one of the most common causes of general osteopenia. In this study, quantitative computed tomography (QCT) was used to compare the bone mineral densities (BMD) between 39 normal dogs and 8 dogs with HAC (6 pituitary-dependent hyperadrenocorticism [PDH]; pituitary dependent hyperadrenocorticism, 2 adrenal hyperadrenocorticism [ADH]; adrenal dependent hyperadrenocorticism) diagnosed through hormonal assay. A computed tomogaraphy scan of the 12th thoracic to 7th lumbar vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…The BMD values obtained using QCT were the highest at L5 in the lumbar vertebrae, which is consistent with a previous study [ 19 ]. The vertebral BMD was similar between QCT and DXA, but the femoral BMD was higher in QCT than in DXA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The BMD values obtained using QCT were the highest at L5 in the lumbar vertebrae, which is consistent with a previous study [ 19 ]. The vertebral BMD was similar between QCT and DXA, but the femoral BMD was higher in QCT than in DXA.…”
Section: Discussionsupporting
confidence: 92%
“…No comparative studies of QCT and DXA have been reported, including any comparison of the femur and vertebrae. In veterinary medicine, more reports have focused on QCT than on DXA [ 3 , 8 , 19 , 25 , 26 ], and although the accessibility of QCT in veterinary clinical practice is greater than that of DXA, no reports have addressed the accuracy and usefulness of QCT. Therefore, the value of QCT in veterinary medicine requires evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the measured HU, the BMD (milligrams/centimeters cubed) was estimated with the use of a customized mineral reference phantom (Computerized Imaging Reference Systems, Norfolk, Virginia) that contained multiple calibration objects with different densities (between 400 and 1750 mg/cm 3 calcium hydroxyapatite) and a phantom‐derived linear regression equation, as previously described . The HU values were converted to BMD for the medial, lateral, cranial and caudal (BMD med , BMD lat , BMD cran and BMD caud , respectively), cortices and a mean cross‐sectional BMD (mBMD) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Another important predictor of bone strength is bone mineral density (BMD), a variable that can be used to evaluate skeletal integrity with respect to mineral content and to determine the risk for osteoporotic fractures . Assessment of BMD through the measurement of Hounsfield units (HU) from CT has become a valuable tool in veterinary medicine in recent years, providing an avenue to evaluate bone quality in a noninvasive manner . From a mechanical perspective, the rigidity and strength of long bones is determined by both the amount of mineralized tissue (ie, mineral content or BMD) and the distribution of the mineralization in space …”
Section: Introductionmentioning
confidence: 99%